BAKTERI PENYERAP LOGAM TIMBAL (Pb) DARI SEDIMEN DAN KERANG HIJAU, DI LAUT BANYU URIP UJUNG PANGKAH, GRESIK - Firmani, Ummul; Safitri, Nur Maulida (Program Studi Akuakultur, Universitas Bangka Belitung, 2023)
Green mussels (Perna viridis) in Banyu Urip Village, Ujung Pangkah Gresik District, have great potential to be developed due to the abundant availability of seeds in nature, easy cultivation methods, namely using floating net cages and step nets, and high market demand. One of the issues with green mussels is the high content of the heavy metal Lead (Pb) in their flesh, which is caused by heavy metal accumulation in the waters. The goal of this study was to isolate, characterize, and test the ability of heavy metal Lead-Pb bacteria to biosorb heavy metal Pb in post-harvest green mussels from sediments and green mussels in the Banyu urip Ujung Pangkah Gresik Sea. The stages of the research included sampling, isolation, macroscopic and microscopic characterization, in vitro testing of Pb heavy metal absorbent. The results showed 6 bacterial isolates, namely two from green mussels coded K1 and K2 and 4 bacterial isolates from marine sediments coded S1, S2, S3 and S4. The six bacterial isolates obtained macroscopic and microscopic characteristics and have been shown in vitro to be able to grow in Nutrient agar enriched 0.8 mg/L Pb(NO3)2.